A GYSEV Zrt. Személyszállítási Üzletágának elemzése - Tóth Tamara Debóra (2020)
In Hungary, the task of rail passenger transport is to satisfy the needs of the national economy and freight. The modernization of the railway, contributes greatly to increasing the travelling standards. The addition of modern vehicles, a favorable timetable, and safe travel contribute significantly to the continuous development of railways. GYSEV Zrt. is a modern railway company that provides the backbone of public transport in the Western Transdanubia region and Eastern Austria. The company acts as kind of a catalyst in the transport of the province, which accompanies the creation of a passage between the transport branches. The scope of activities of GYSEV Zrt. is ex-tremely wide, because it is also present in hospitality and real estate management. The main topic of my final thesis is the economic analysis of the Passenger Transport of GYSEV Zrt., through the examination of the profitability situation and the analysis of efficiency. Using the performances and data, I compared the Passenger Transport Business Unit to the operation of the Hungarian plant of GYSEV Zrt. To per-form my analysis, I used the company's public annual reports (balance sheet, income statement, public service and non-public service activity, and performance statement). During the evaluation of the obtained results, I established the profitability and efficiency situation of the Passenger Transport Group. In the analysis of profitability, I used, among other things, operating profit as a proportion of assets, as a proportion of equity, as a proportion of sales, and as a result of a number of employees. Using the indicators listed above, I obtained a comprehensive statement of the profitability situation of the Business Unit. To present the efficiency situation, I used the turnover rate of inventories, the demanding nature of tangible assets, and cost-effectiveness. The calculation of cost-effectiveness indicators was not smooth, as the organization’s expenses are extremely high but its net production values are significantly low. I then continued the analysis with the help of ratios, for which I mainly used distribution ratios. In terms of distribution, I compared the group's sales revenue, expenses, number of employees and investments to the Hungarian part of GYSEV Zrt. The company's investments and expenses are outstanding, while the investments of the Business Unit are particularly insignificant but its expenses make up the entire amount of corporate expenses. Finally, I examined the annual passenger transport performance and the distribution ratios of internal expenditures.